Influence of oncam feature in online conference on learning motivation during the pandemic - Muchammad Zidan Maulana; Azzahra Putri Dewanto (Universitas Pendidikan Indonesia, 2022)
The impact of the COVID-19 pandemic has affected various aspects, including education. Since the pandemic, students have been forced to do online learning. Students’ unpreparedness for this change resulted in less effective teaching and learning activities. The students become inactive and find it difficult to focus during class. This, of course, affects using the oncam feature on the level of student learning motivation during the current pandemic. In this study, the researcher used a quantitative method by using a research instrument in the form of a form containing a series of questions related to how respondents’ learning behavior was while undergoing an online learning process using an online conference application that provides an oncam feature. Participants in this study were 42 active students at the Indonesian Education University, Department of Educational Curriculum and Technology batch 2020. Based on the data obtained, it was shown that the oncam feature could affect respondents' motivation level in learning. Therefore, according to these findings, the oncam feature in online learning can be paid more attention to maintain student learning motivation so that the learning process can run optimally.